Influence of Media–Thermal Ageing on the Long‐Term Creep Behavior of Polypropylene. Issue 1 (19th June 2022) - Berthold, Anja; Mathew, Kuriakose; Lach, Ralf; Langer, Beate
Abstract: Plastic components subjected to a constant load, such as pipes or load‐bearing structures in motor vehicles, tend to creep and show increased deformation over time. In special applications for example coolant expansion tanks, increased temperatures and media also affect the long‐term creep behavior. In this study, the influence of media–thermal aging on the long‐term creep behavior is investigated for predicting service life.